Identity Transitions: Worker Displacement and Identity Management - Mulder, Allen Marvin (My University, 1995)
Studies of plant closure and worker displacement have examined the more quantifiable impacts of these events. Rarely have these studies touched on the subjective impacts of worker displacement. One such impact is on the identity of the worker. People form major parts of their identities around the work which they do. Thus, when they face a change in their work there is also a change in their identities. This study has focused on how workers have managed their identities in light of their displacement due to the closures of a brewery and a distillery in southern Ontario.
It was found that workers maintained their social identities while changing their personal identities. It was also discovered that personal identities could be sub-divided into qualitatively different categories: positional attributes associated with role, and personal qualities associated with one's broader character. These sub-groups were altered in the identity management process but the catalyst for each change was different.
In all, this thesis contributes to the understanding of the subjective elements of plant closure and worker displacement. There are several avenues for further study indicated by the findings of this project.
Keywords: sociology; Sociology; Sociology